Fiqh Al-Hadis: Studi Terhadap Hadis Membaca Al-Fatihah Bagi Makmum Pada Majalah Soerti - Kia Mudin; Edi Safri; Zulfikri Zulfikri; Edriagus Saputra (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Soearti Magazine is a forum for polemic between Tarbiyah Islamiyah and those who attacked it. They answered the polemics that occurred at that time by including the Prophet's traditions, translations, names of narrators, and their understanding.However, the hadiths they wrote were only at the level of friends, some were not even mentioned, there was an error in writing the mind and not all hadiths that were explained in their veracity.This study aims to trace honesty and analyze the understanding of the hadiths contained in Soearti magazine on the theme of Reading al-Fatihah for the general public. The method used in this research is descriptive-qualitative method.From the results of this study, the Hadith that discusses reading al-Fatihah for the congregation in Soearti magazine, there are 7 hadiths consisting of 5 authentic quality hadiths and 2 dha'if quality hadiths, so that all of these traditions can be used as evidence and put into practice.The hadiths in Soearti Magazine are understood using textual and contextual methods of understanding but tend to use textual methods. Meanwhile, the style of understanding in the Hadith is traditional.